Composite diaphragm, preparation and application thereof and zero-gap alkaline water electrolysis device
By uniformly growing hydrophilic layered inorganic nanoparticles on the Daramic porous base film, the problems of low mechanical strength and high gas permeability in the zero-gap alkali-water electrolysis technology are solved, and higher electrolytic efficiency and product purity are achieved.
Patent Information
- Application Number
- CN202311240385.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
In the existing zero-gap alkali-water electrolysis technology, the separator has low mechanical strength and is easily pierced by the electrode, and increasing porosity or reducing thickness to reduce the membrane surface resistance will lead to transmembrane penetration of gas products and reducing product purity.
Hydrophilic layered inorganic nanoparticles with good alkali resistance are uniformly grown on the membrane pores and membrane surface of the Daramic pore base film. The membrane pores are supported by inorganic particles, the mechanical strength of the membrane is enhanced, and the gas transmembrane permeability is reduced by high repulsive hydrophilic nanoparticles.
It is realized that the mechanical strength and gas barrier capacity of the separator are improved in the zero-gap alkali-water electrolytic device, the electrolytic efficiency and product purity are improved, and the electrolytic energy consumption is reduced.
Smart Images

Figure CN119685877A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite diaphragm material for zero-gap alkaline water electrolysis and preparation and application thereof, and in particular to application of the diaphragm in a zero-gap alkaline water electrolysis device. Background Art
[0002] In recent years, under the background of global response to climate change and accelerated energy transformation, hydrogen, as a clean energy, is expected to help achieve the goal of global carbon-free energy and solve the increasingly serious global energy shortage and environmental pollution. As an energy carrier with high weight energy density, hydrogen is not only conducive to the large-scale and efficient storage and consumption of other renewable energy sources, but also widely used in various industries such as metallurgy, medical treatment, electronics, and food. It has become an indispensable and important resource in today's society. Compared with the high-energy consumption and high-pollution chemical steam reforming hydrogen production, the use of electricity for water electrolysis to produce hydrogen has the advantages of high energy utilization efficiency, high product yield, and low environmental pollution. By using it in conjunction with green and clean energy power generation, it is expected to achieve zero pollution and zero emissions.
[0003] Among the many methods of producing hydrogen by water electrolysis, alkaline water electrolysis (ALKWE) technology is the most mature. The corresponding electrolyzer has low manufacturing cost, long life, large scale, high hydrogen purity and easy operation. However, in the alkaline water electrolyzer, in order to reduce the transmembrane permeability of the gas, the electrode needs to maintain a certain distance from the diaphragm. A slight increase in the distance between the electrodes will cause the internal resistance of the electrolyzer to increase sharply. In addition, during the electrolysis process, the product hydrogen and oxygen will be directly adsorbed on the active surface of the electrode in the form of bubbles, reducing the active sites of the electrode and also causing the internal resistance of the electrolyzer to increase.
[0004] In view of this, the technology of "zero-gap alkaline water electrolyzer" has attracted more and more attention. Zero-gap alkaline water electrolyzer is a type of alkaline water electrolysis hydrogen production. In the zero-gap alkaline water electrolyzer, the positive and negative electrodes are tightly combined on both sides of the diaphragm to reduce the distance between the electrodes. At the same time, this design can also prevent the product bubbles from being adsorbed on the active surface of the electrode, which is conducive to greatly reducing the internal resistance of the electrolyzer and improving the electrolysis efficiency.
[0005] However, the current zero-gap alkaline water electrolysis technology is still immature, and the materials used in traditional alkaline water electrolysis cannot be directly used in zero-gap electrolysis systems. The development of technology is still subject to the following problems:
[0006] (1) The mechanical strength of the diaphragm is low. When the metal electrodes are tightly attached to both sides of the diaphragm, the diaphragm is easily punctured, causing a short circuit in the electrolytic cell.
[0007] (2) Although increasing the membrane porosity or reducing the membrane thickness can reduce the membrane surface resistance, it is also easy to cause gas products to permeate across the membrane and reduce the product purity. Summary of the invention
[0008] In view of the above key technical problems, the present invention aims to provide a zero-gap alkaline water electrolysis diaphragm and its preparation method and application. This type of diaphragm uniformly grows hydrophilic layered inorganic nanoparticles with good alkali resistance in the membrane pores and membrane surface of the Daramic porous base membrane, while reducing the membrane surface resistance, using inorganic particles to support the membrane pores and enhance the mechanical strength of the membrane. In addition, the hydrophilic nanoparticles in the membrane pores and on the membrane surface have a high repulsion to the gas products of electrolysis, which can effectively reduce the gas transmembrane permeability, improve the product purity, and reduce the energy consumption of electrolysis.
[0009] The purpose of the present invention can be achieved by the following technical solutions:
[0010] 1. An object of the present invention is to provide an alkali-resistant composite diaphragm for use in a zero-gap alkaline water electrolysis device, wherein the alkali-resistant composite diaphragm comprises a porous base membrane and hydrophilic nanoparticles grown in situ on the base membrane; wherein the inorganic nanoparticles are uniformly grown in the membrane pores and on the membrane surface of the base membrane.
[0011] In the alkali-resistant composite diaphragm described in the present invention, the inorganic nanoparticles are layered hydrophilic particles with good alkali resistance and stability. By controlling the growth amount of the particles on the base membrane, the mechanical strength, ionic conductivity and gas barrier rate of the diaphragm can be enhanced, thereby achieving simultaneous improvement in the electrolysis efficiency and stability of the diaphragm.
[0012] 2. The second object of the present invention is to provide a method for preparing the alkali-resistant composite diaphragm described in the first object, the preparation method comprising the following steps:
[0013] (1) dissolving an inorganic metal salt in ultrapure water to obtain an inorganic metal salt solution;
[0014] (2) soaking the cleaned Daramic base film in the inorganic metal salt solution in step (1);
[0015] (3) adding nitrogen-containing organic matter or ammonium salt to the solution in step (2), and then performing a solvothermal reaction;
[0016] (4) Soaking the composite membrane obtained in step (3) in a potassium hydroxide solution, then washing with a solvent and drying to obtain the alkali-resistant porous composite membrane.
[0017] The inorganic metal salt in step (1) is a combination of a divalent metal salt and a trivalent metal salt; the metal ion concentration ratio of the divalent metal salt and the trivalent metal salt is 2:1 or 4:1; wherein the divalent metal salt is one or two of magnesium salt, cobalt salt, nickel salt, and zinc salt; and the trivalent metal salt is one or two of aluminum salt, iron salt, and chromium salt.
[0018] The inorganic metal salt in step (1) is selected from nitrate, sulfate and chloride.
[0019] Preferably, the weight percentage of the inorganic salt is 10% to 15%, for example, 10%, 11%, 12%, 13%, 14%, 15%, etc., but is not limited to the listed values, and other unlisted values within the above range are also applicable.
[0020] Preferably, the divalent inorganic metal salt is magnesium nitrate, the trivalent inorganic metal salt is aluminum nitrate, and the ratio of magnesium nitrate to aluminum nitrate is controlled to be 2:1.
[0021] In the step (2), the thickness of the daramic base film is between 150 μm and 900 μm, the porosity is between 52% and 70%, and the pore size distribution range is between 0.001 nm and 600 nm.
[0022] In step (2), the Daramic membrane needs to be cleaned before being immersed in the inorganic metal salt solution in step (1). The cleaning step is to immerse the Daramic membrane in a mixed solution of ethanol and methanol in a mixing ratio of 2:1 (60°C, immersion for 3 hours), and then immerse it in ultrapure water (70°C, immersion for 3 hours), and repeat it three times.
[0023] In the step (2), the solvent thermal reaction temperature is 90° C. to 150° C., and the reaction time is 24 hours to 72 hours. If the reaction time exceeds this range, the hydrophilic inorganic particles may not grow completely or the porous base film may be damaged.
[0024] Preferably, the reaction time is 48 hours.
[0025] Preferably, the reaction temperature is 100°C to 110°C, for example, it can be 100°C, 101°C, 102°C, 103°C, 104°C, 105°C, 106°C, 107°C, 108°C, 109°C, 110°C, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0026] In the step (4), the membrane after the solvent thermal reaction needs to be immersed in a potassium hydroxide solution; the concentration of the potassium hydroxide solution is 1 mol·L -1 ~3mol·L -1 The soaking temperature is 30℃~50℃, and the soaking time is 48 hours to 96 hours.
[0027] Preferably, the concentration of potassium hydroxide solution is 3 mol·L -1 The soaking temperature is 40℃ and the soaking time is 96 hours.
[0028] In the step (4), the composite diaphragm soaked in the potassium hydroxide solution is thoroughly washed with a solvent and dried; the drying temperature is 30° C. to 60° C., and the drying time is 48 hours to 96 hours.
[0029] Preferably, the drying temperature is 30°C.
[0030] 3. The third object of the present invention is to provide an application of the above object one alkali-resistant composite diaphragm for electrolyzing water to produce hydrogen and oxygen, specifically a zero-gap alkaline water electrolysis device.
[0031] The zero-gap alkaline water electrolysis device comprises a cathode end plate, a porous cathode gas diffusion electrode (GDE-cathode), the alkali-resistant composite diaphragm described in purpose 1, a felt-like anode gas diffusion electrode (GDE-anode), and an anode end plate, which are arranged in sequence; wherein the porous cathode gas diffusion electrode and the felt-like anode gas diffusion electrode are hot-pressed on both sides of the alkali-resistant composite diaphragm described in claim 1, respectively.
[0032] Optionally, the cathode end plate material is one of high-purity graphite plate, N4 high-purity nickel plate, TA2 titanium plate and 904L stainless steel plate; the anode end plate material is one of N4 high-purity nickel plate with a 2μm platinum layer on the surface, TA2 titanium plate with a 2μm platinum layer on the surface, 904L stainless steel plate with a 2μm platinum layer on the surface, and Hastelloy C276 with a 2μm platinum layer on the surface.
[0033] The porous cathode gas diffusion electrode is made of nickel foam with a nickel-based catalyst sprayed on the surface; the felt-shaped anode gas diffusion electrode is a titanium felt with a 50nm-2μm platinum layer plated on the surface.
[0034] Preferably, the porosity of the nickel foam in the porous cathode gas diffusion electrode is 96%, the thickness is 0.32mm-0.4mm, and the catalyst is Raney nickel; the platinum coating thickness in the felt anode gas diffusion electrode is 2μm, the titanium felt thickness is 250μm, and the porosity is 50%-60%.
[0035] The porous cathode gas diffusion electrode and the felt-like anode gas diffusion electrode in the zero-gap alkaline water electrolysis device are hot-pressed on both sides of the alkali-resistant composite diaphragm described in the first purpose respectively.
[0036] Preferably, the hot pressing temperature is 140° C. and the hot pressing time is 40 seconds.
[0037] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0038] The alkali-resistant composite diaphragm of the present invention comprises a porous base film and two-dimensional layered inorganic particles grown in situ in the membrane pores and the membrane surface, wherein the porous base film is a commercial Daramic membrane, and the layered inorganic particles are hydrophilic nanoparticles with good alkali resistance, and are uniformly grown in the membrane pores and the membrane surface. The alkali-resistant composite diaphragm of the present invention is low in cost, and has good mechanical strength and high alkali resistance stability, and can maintain a long life in the high alkali concentration environment required for alkaline water electrolysis (ALKWE). In addition, by controlling the structure of the nanoparticles and the amount of their growth in the membrane pores and the membrane surface, the gas permeation problem of the porous diaphragm material can be effectively solved, so that it can be used in a zero-gap alkaline water electrolyzer, while reducing the distance between the electrodes on both sides of the diaphragm and improving the electrolysis efficiency, the stability of the electrolyzer is improved.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The present invention realizes the in-situ growth of two-dimensional hydrophilic nanoparticles in a daramic porous membrane for the first time. By controlling the reaction conditions, the growth amount and growth morphology of the particles in the membrane can be controlled, thereby achieving regulation of the properties of the composite membrane.
[0041] (2) The Daramic membrane used in the present invention is low-cost and highly stable and can be purchased commercially; the raw materials of the hydrophilic nanoparticles are inexpensive, and the growth process of the particles is controllable, the particles are highly alkali-resistant and stable, and they interact strongly with the base membrane and are not easy to fall off; the composite membrane preparation process is simple, which meets the needs of large-scale applications and shows good application prospects.
[0042] (3) The present invention realizes for the first time the use of Daramic membrane as a substrate to prepare a composite diaphragm with good alkali resistance, and applies it to an alkaline water electrolysis device for the first time. The related alkaline water electrolysis device shows excellent stability, which broadens the selection range of alkali-resistant diaphragms for alkaline water electrolysis.
[0043] (4) The present invention realizes the use of layered nanoparticles to support the porous structure of the Daramic membrane, thereby improving the mechanical strength of the Daramic membrane-based porous composite diaphragm.
[0044] (5) The present invention utilizes hydrophilic nanoparticles to enhance the gas barrier capability of the porous membrane, so that it can be used in a zero-gap alkaline water electrolyzer to prevent hydrogen and oxygen at the positive and negative electrodes from crossing the membrane and improve the purity of the hydrogen product. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Microscopic morphology of the alkali-resistant composite diaphragm prepared in Example 1, and the corresponding element distribution;
[0046] Figure 2 A magnified microscopic image of the alkali-resistant composite diaphragm prepared in Example 1; Figure 2a is magnified 8000 times, Figure 2 b is magnified 30,000 times;
[0047] Figure 3 Thermogravimetric test results of the alkali-resistant composite diaphragm and the Daramic porous base membrane prepared in Example 1;
[0048] Figure 4 Comparison of mechanical strengths of the alkali-resistant composite diaphragm prepared in Example 1 and the Daramic porous base membrane;
[0049] Figure 5 A schematic diagram of an example of a zero-gap alkaline water electrolysis device of the present invention; in the figure, the numbers are: 1 is the cathode end plate; 2 is the diaphragm; 3 is the anode end plate; 4 is the cathode gas diffusion electrode; and 5 is the anode diffusion electrode. DETAILED DESCRIPTION
[0050] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0051] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0052] Example 1
[0053] Alkali-resistant composite diaphragm preparation process:
[0054] (1) A. A commercial Daramic porous membrane (membrane area of 5 cm×5 cm) with a thickness of 180 μm, a pore size distribution range of 0.001 nm to 600 nm, and a porosity of 60% was immersed in a mixed solution of ethanol and methanol in a mixed volume ratio of 2:1 at a temperature of 60° C. for 3 hours; B. Subsequently, the Daramic porous base membrane was immersed in ultrapure water at a temperature of 70° C. for 3 hours.
[0055] Repeat the above steps A and B three times to obtain a cleaned Daramic porous base membrane.
[0056] (2) Prepare an inorganic metal salt solution: Dissolve 0.06 mol magnesium nitrate and 0.03 mol aluminum nitrate in 60 mL ultrapure water. After the inorganic salt is completely dissolved, soak the cleaned Daramic porous base membrane in the inorganic salt solution at 60°C for 10 hours. After the solution is cooled to room temperature, add 0.42 mol urea to the solution and sonicate for 1 hour to allow the nanoparticle precursor to fully penetrate into the porous structure of the Daramic membrane.
[0057] (3) The Daramic membrane with the precursor in the pores and the urea-containing soaking solution in step (2) were transferred to a stainless steel autoclave (100 mL) lined with polytetrafluoroethylene (Teflon) and subjected to a solvothermal reaction at 110° C. for 48 hours.
[0058] (4) After the solvothermal reaction, the obtained composite membrane was immersed in 3 mol·L -1 The immersion temperature in the potassium hydroxide solution was 40°C and the immersion time was 96 hours. Subsequently, the composite membrane was cleaned with an ethanol water (volume concentration 1:4) solution and dried at 50°C for 72 hours to obtain a Daramic-based alkali-resistant composite membrane.
[0059] The microstructure of the alkali-resistant composite diaphragm was observed using a scanning electron microscope ( Figure 1 ), the thickness of the alkali-resistant composite diaphragm is 170μm, which is less than the thickness of the Daramic base membrane (180μm), indicating that the Daramic base composite membrane obtained by the composite membrane preparation method of the present invention will become thinner. Through elemental analysis comparison, it can be clearly observed that the hydrophilic layered nanoparticles are uniformly dispersed in the membrane. Magnifying the observation magnification of the scanning electron microscope, it is observed that the structure of the inorganic nanoparticles is a two-dimensional layered structure (the layer of a single layer unit cell is 0.5nm×0.5nm~1.5nm×1.5nm; the thickness of a single layer unit cell is 5~30nm), and it grows uniformly in the membrane and on the membrane surface, with a particle size of 10~50 nanometers ( Figure 2 a is magnified 8000 times, Figure 2 b is magnified 30000 times). The thermal stability of the film was analyzed by thermogravimetry. Figure 3 The films were shown to be thermally stable at 200°C. Figure 4 The mechanical strength comparison test of the diaphragm showed that the alkali-resistant composite diaphragm had a greater tensile strength than the Daramic porous base membrane, and the elongation at break was lower. -1 Potassium hydroxide solution (80°C), by regularly measuring the percentage of mass loss of the membrane (the percentage of membrane mass loss to the initial weight before alkali solution), the alkali stability of the membrane was analyzed. The results showed that the composite membrane could remain stable for 500 hours (Table 1). The membrane was tested for gas barrier properties on a gas diffuser. The results showed that the commercial Daramic membrane had poor gas barrier properties, and gas on both sides of the membrane would also interleave under the condition of 0 pressure difference. In the test of the alkali-resistant composite membrane grown with lamellar nanoparticles, the gas interleave ratio was less than one thousandth under the pressure difference of 0.05MPa, proving that after the growth of the layered particles, the composite membrane has better gas barrier properties.
[0060] Table 1
[0061]
[0062] The prepared alkali-resistant composite diaphragm was installed in a zero-gap alkaline water electrolysis device: First, a porous cathode gas diffusion electrode (surface sprayed with Raney nickel foam, where the area of the foam nickel is 2×2 cm 2 , porosity is 96%, thickness is 0.4mm, Raney nickel is 1.5mg / cm 2 ;) and a felt-shaped anode gas diffusion electrode (platinum-plated titanium felt, wherein the platinum coating thickness is 2 μm, the titanium felt thickness is 250 μm, and the area is 2×2 cm 2 , porosity of 60%) were hot pressed on both sides of the alkali-resistant composite diaphragm (the hot pressing pressure was 2 MPa, the temperature was 140°C, the hot pressing time was 40 seconds, and the membrane area was 4◇4 cm 2 ).
[0063] Then, the cathode end plate (TA2 titanium plate), porous cathode gas diffusion electrode, the Daramic-based alkali-resistant composite diaphragm, felt-shaped anode gas diffusion electrode, and anode end plate (TA2 titanium plate with platinum coating on the surface near the porous anode gas diffusion electrode, with a platinum coating of 2 μm) were tightly stacked and connected together to assemble a zero-gap electrolysis device. Subsequently, 6 mol·L -1 Potassium hydroxide solution (flow rate of 10 mL / min) was used for electrolysis performance test at 80°C. The electrolysis performance was 1.8 V electrolysis voltage and the current density was 750 mA cm -2 .
[0064] Comparative Example 1
[0065] The process and conditions are the same as those of Example 1, except that after the Daramic porous membrane is cleaned according to the method of step (1) in Example 1, it is directly transferred into a stainless steel autoclave (100 mL) lined with polytetrafluoroethylene (Teflon), 60 mL of ultrapure water is added to the autoclave, and the temperature is maintained at 110° C. for 72 hours. After the end, the Daramic porous membrane is taken out. The obtained membrane is treated according to the method of step (4) in Example 1 to obtain a comparative membrane 1. The rest of the membrane assembly into the zero-gap alkaline water electrolysis device and the test operation method are the same as in Example 1.
[0066] Comparative Example 2
[0067] The process and conditions are the same as those in Example 1, except that after completing step (1) and step (2), the Daramic porous base membrane soaked in the mixed solution of magnesium nitrate and aluminum nitrate and the urea-containing soaking solution are transferred into a stainless steel autoclave (100 mL) lined with polytetrafluoroethylene (Teflon) and maintained at 30°C for 72 hours. Subsequently, the membrane is taken out and cleaned with ethanol aqueous solution, and the membrane treatment is completed according to step (4) in Example 1 to obtain comparative membrane 2. The remaining operation methods of assembling the membrane into the zero-gap alkaline water electrolysis device and testing are the same as those in Example 1.
[0068] Comparative Example 3
[0069] The process and conditions are the same as those of Example 1, except that after the Daramic porous membrane is cleaned according to the method of step (1) in Example 1, the membrane is directly immersed in 3 mol·L -1 The immersion temperature in the potassium hydroxide solution was 40° C. and the immersion time was 96 hours. Subsequently, the composite diaphragm was cleaned with an ethanol aqueous solution to obtain a comparative membrane 3. The rest of the membrane assembly was assembled into a zero-gap alkaline water electrolysis device and the test operation method was the same as in Example 1.
[0070] Comparative Example 4
[0071] The process and conditions are the same as those in Example 1, except that after the Daramic porous membrane is cleaned according to the method of step (1) in Example 1, no other operation is performed to directly obtain the comparative membrane 4. The rest of the operation methods of assembling the membrane into the zero-gap alkaline water electrolysis device and testing are the same as those in Example 1.
[0072] Comparative Example 5
[0073] The process and conditions are the same as those of Example 1, except that, after completing step (1) and step (2) according to the operating method of Example 1, the Daramic porous base membrane soaked in the mixed solution of magnesium nitrate and aluminum nitrate and the soaking solution are transferred into a stainless steel autoclave (100 mL) lined with polytetrafluoroethylene (Teflon), without adding urea, but directly solvent-thermally reacting the membrane at 110°C for 72 hours. Subsequently, the membrane is taken out, cleaned with ethanol aqueous solution, and the membrane treatment is completed according to step (4) in Example 1 to obtain a comparative membrane 5. The remaining operating methods of assembling the membrane into a zero-gap alkaline water electrolysis device and testing are the same as those of Example 1.
[0074] Example 2
[0075] The process and conditions are the same as those in Example 1, except that after the Daramic porous membrane is cleaned according to the method in step (1) of Example 1, the membrane is immersed in 60 mL of 1 mol·L -1 l magnesium chloride and 0.5 mol·L-1 The mixed aqueous solution of aluminum chloride was immersed at 60°C for 10 hours. The Daramic porous base membrane was then taken out and the membrane treatment was completed according to the method of step (3) and step (4) in Example 1 to obtain a comparative membrane 6. The rest of the membrane assembly was assembled into a zero-gap alkaline water electrolysis device and the test operation method was the same as in Example 1.
[0076] Comparative Example 6
[0077] The process and conditions are the same as those in Example 1, except that, after completing step (1) and step (2) according to the operating method of Example 1, the Daramic porous base membrane soaked in the mixed solution of magnesium nitrate and aluminum nitrate and the urea-containing soaking solution are transferred into a stainless steel autoclave (100 mL) lined with polytetrafluoroethylene (Teflon) and subjected to solvent thermal reaction at 140°C for 72 hours. After the reaction is completed, the membrane is taken out and cleaned with ethanol aqueous solution, and the membrane treatment is completed according to step (4) in Example 1 to obtain comparative membrane 7. The remaining operating methods of assembling the membrane into the zero-gap alkaline water electrolysis device and testing are the same as those in Example 1.
[0078] Comparative Example 7
[0079] The process and conditions are the same as those in Example 1, except that, after completing step (1) and step (2) according to the operating method of Example 1, the Daramic porous base membrane soaked in the mixed solution of magnesium nitrate and aluminum nitrate and the urea-containing soaking solution are transferred into a stainless steel high-pressure reactor (100 mL) lined with polytetrafluoroethylene (Teflon) and subjected to solvent thermal reaction at 110°C for 24 hours. After the reaction is completed, the membrane is taken out and cleaned with ethanol aqueous solution, and the membrane treatment is completed according to step (4) in Example 1 to obtain a comparative membrane 8. The rest of the membrane assembly is assembled into a zero-gap alkaline water electrolysis device and the operating method of the test is the same as in Example 1.
[0080] Comparative Example 8
[0081] The process and conditions are the same as those in Example 1, except that, after completing step (1) and step (2) according to the operating method of Example 1, the Daramic porous base membrane soaked in the mixed solution of magnesium nitrate and aluminum nitrate and the urea-containing soaking solution are transferred into a stainless steel autoclave (100 mL) lined with polytetrafluoroethylene (Teflon) and subjected to solvent thermal reaction at 140°C for 24 hours. After the reaction is completed, the membrane is taken out and cleaned with ethanol aqueous solution, and the membrane treatment is completed according to step (4) in Example 1 to obtain a comparative membrane 9. The remaining operating methods of assembling the membrane into a zero-gap alkaline water electrolysis device and testing are the same as those in Example 1.
[0082] Comparative Example 9
[0083] The process and conditions are the same as those in Example 1, except that after completing step (1), step (2) and step (3) according to the operating method of Example 1, a diaphragm prepared by a solvent thermal reaction is obtained, which is cleaned with an ethanol aqueous solution and dried to obtain a comparative membrane 10. The remaining operating methods of assembling the membrane into a zero-gap alkaline water electrolysis device and testing are the same as those in Example 1.
[0084] Comparative Example 10
[0085] The process and conditions are the same as those in Example 1, except that the alkali-resistant composite diaphragm is prepared according to the operating method of Example 1. The prepared alkali-resistant composite diaphragm is directly assembled into a zero-gap water electrolysis device, except that the composite diaphragm is not hot-pressed with the cathode and anode gas diffusion electrodes before the alkali-resistant diaphragm is installed. The remaining operations are the same as those in Example 1.
[0086] Comparative Example 11
[0087] The process and conditions are the same as those in Example 1, except that an alkali-resistant composite diaphragm is obtained according to the operating method of Example 1. Subsequently, the obtained alkali-resistant composite diaphragm is hot-pressed with the gas diffusion electrodes on both sides of the cathode and the anode, with a hot-pressing pressure of 10 MPa, a temperature of 140° C., and a hot-pressing time of 40 seconds. After hot-pressing, the zero-gap alkaline water electrolysis device is assembled according to Example 1, and the remaining operations are the same as those in Example 1.
[0088] Comparative Example 12
[0089] The process and conditions are the same as those in Example 1, except that an alkali-resistant composite diaphragm is obtained according to the operating method of Example 1. Subsequently, the obtained alkali-resistant composite diaphragm is hot-pressed with the gas diffusion electrodes on both sides of the cathode and the anode, with a hot-pressing pressure of 2 MPa, a temperature of 140° C., and a hot-pressing time of 3 minutes. After hot-pressing, the zero-gap alkaline water electrolysis device is assembled according to Example 1, and the remaining operations are the same as in Example 1.
[0090] Comparative Example 13
[0091] According to the operation method of Example 1, an alkali-resistant composite diaphragm was obtained. Subsequently, the obtained alkali-resistant composite diaphragm was hot-pressed with the gas diffusion electrodes on both sides of the cathode and the anode, and the hot-pressing pressure was 2 MPa, the temperature was 30°C, and the hot-pressing time was 40 seconds. After hot-pressing, the zero-gap alkaline water electrolysis device was assembled according to Example 1, and the remaining operation process and conditions were the same as those in Example 1.
[0092] Comparative Example 14
[0093] The process and conditions are the same as those in Example 1, except that an alkali-resistant composite diaphragm is obtained according to the operating method of Example 1. Subsequently, the obtained alkali-resistant composite diaphragm is hot-pressed with the gas diffusion electrodes on both sides of the cathode and anode, with a hot pressing pressure of 2MPa, a temperature of 140°C, and a hot pressing time of 40 seconds. After hot pressing, an electrolysis device is assembled according to the cathode end plate (TA2 titanium plate), a porous cathode gas diffusion electrode, the alkali-resistant composite diaphragm, a felt anode gas diffusion electrode, and an anode end plate (TA2 titanium plate with platinum coating on the surface, and a platinum coating of 2μm) arranged in sequence. The remaining operating processes and conditions are the same as those in Example 1.
[0094] Example 3
[0095] The process and conditions are the same as those in Example 1, except that an alkali-resistant composite diaphragm is obtained according to the operating method of Example 1. Subsequently, the obtained alkali-resistant composite diaphragm is hot-pressed with the gas diffusion electrodes on both sides of the cathode and anode, with a hot pressing pressure of 2MPa, a temperature of 140°C, and a hot pressing time of 40 seconds. After hot pressing, an electrolysis device is assembled according to the cathode end plate (high-purity graphite plate), a porous cathode gas diffusion electrode, the alkali-resistant composite diaphragm, a felt-like anode gas diffusion electrode, and an anode end plate (TA2 titanium plate with platinum coating on the surface, and a platinum coating of 2μm) arranged in sequence. The remaining operating processes and conditions are the same as those in Example 1.
[0096] Example 4
[0097] The process and conditions are the same as those in Example 1, except that an alkali-resistant composite diaphragm is obtained according to the operating method of Example 1. Subsequently, the obtained alkali-resistant composite diaphragm is hot-pressed with the gas diffusion electrodes on both sides of the cathode and anode, with a hot pressing pressure of 2MPa, a temperature of 140°C, and a hot pressing time of 40 seconds. After hot pressing, an electrolysis device is assembled according to the cathode end plate (N4 high-purity nickel plate), a porous cathode gas diffusion electrode, the alkali-resistant composite diaphragm, a felt-like anode gas diffusion electrode, and an anode end plate (TA2 titanium plate with platinum coating on the surface, and a platinum coating of 2μm) arranged in sequence. The remaining operating processes and conditions are the same as those in Example 1.
[0098] Example 5
[0099] The process and conditions are the same as those in Example 1, except that an alkali-resistant composite diaphragm is obtained according to the operating method of Example 1. Subsequently, the obtained alkali-resistant composite diaphragm is hot-pressed with the gas diffusion electrodes on both sides of the cathode and anode, and the hot pressing pressure is 2MPa, the temperature is 140°C, and the hot pressing time is 40 seconds. After hot pressing, the electrolysis device is assembled according to the cathode end plate (TA2 titanium plate), the porous cathode gas diffusion electrode, the alkali-resistant composite diaphragm, the felt anode gas diffusion electrode, and the anode end plate (N4 high-purity nickel plate with platinum coating on the surface, and the platinum coating is 2μm) arranged in sequence. The remaining operating processes and conditions are the same as in Example 1.
[0100] The alkali-resistant composite diaphragm and the zero-gap alkaline water electrolysis device were tested:
[0101] (1) The membrane surface resistance of the diaphragms obtained in the above examples and comparative examples was tested in the following manner:
[0102] The surface resistance of the membrane is tested in an H-shaped electrolytic cell (Tianjin Aida Hengsheng H-type electrolytic cell CH2001-S), and the resistance is calculated based on the slope of the IV curve. The resistance of the electrolytic cell assembled with and without a membrane is measured separately, and the difference between the two is used to calculate the membrane resistance.
[0103] R A =A×(R1-R2)
[0104] Where R A is the surface resistance; A is the effective area of the membrane; R1 and R2 are the resistances of the electrolytic cell with and without the membrane, respectively.
[0105] The membrane surface resistance test results of the diaphragms obtained in the above examples and comparative examples are listed in Table 2.
[0106] (2) The membranes obtained in the above examples and comparative examples were subjected to water electrolysis performance tests, and the test method was as follows:
[0107] 6 mol·L -1 Potassium hydroxide solution, maintain the device temperature at 80℃, control the electrolysis voltage applied to the cathode and anode from 1V to 2V, and the voltage increase rate is 20mV•min -1 , measure the current density during the voltage change process.
[0108] The water electrolysis performance test results of the diaphragms obtained in the above examples and comparative examples are listed in Table 2 (1.8 V corresponds to current density).
[0109] Table 2
[0110]
[0111]
[0112] From Table (2), we can determine the following points:
[0113] (1) As can be seen from Example 1, the alkali-resistant organic composite diaphragm obtained by the present invention has a small membrane surface resistance and a high ion conductivity. When assembled into a corresponding zero-gap alkaline water electrolysis device, it has good electrolysis performance.
[0114] (2) By comparing Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5, it can be seen that the hydrophilic nanoparticles in the composite membrane can enhance the stability of the membrane, and the inorganic nano-ion precursors of nitrate and chloride have little effect on the performance of the composite membrane. However, the membrane without inorganic nanoparticle growth has lower electrolytic performance in the electrolysis device. This is because if the membrane is not supported by nanoparticles, its internal pore structure will collapse in concentrated alkali, causing the surface resistance of the membrane to increase. In addition, the membranes in Comparative Examples 2 and 5 contain inorganic salt precursors, which will not have a significant impact on the surface resistance of the membrane, but will poison the catalyst in the electrolysis device, causing the electrolysis performance to decrease.
[0115] (3) By comparing Example 1, Comparative Example 6, Comparative Example 7, and Comparative Example 8, it can be seen that changing the solvent thermal reaction temperature and duration will affect the growth state of the particles in the membrane. In Comparative Example 6, due to the high reaction temperature, the particles in the membrane are seriously stacked, resulting in an increase in the surface resistance of the diaphragm and a decrease in the electrolysis efficiency; while in Comparative Example 7, the reaction time is too short and the particle growth is insufficient, resulting in a fast pore collapse rate in the alkali and poor stability.
[0116] (4) By comparing Example 3, Example 4, Example 5, and Comparative Example 14, it can be seen that the material of the end plate is closely related to the water electrolysis performance. After the anode end plate is changed to titanium without platinum coating, it will oxidize into titanium oxide under high potential, which increases the resistance of the end plate and causes the electrolysis performance to decrease; while changing the titanium plate with a platinum layer on the surface to a nickel plate with a platinum layer on the surface does not have a significant impact on the performance. For the cathode end plate, nickel plate, titanium plate and graphite plate have little effect on the performance.
Claims
1. A composite diaphragm, characterized in that: The composite diaphragm comprises a porous base membrane and inorganic nanoparticles grown in situ on the base membrane; wherein the inorganic nanoparticles are in a layered structure and are grown in situ in the membrane pores and on the membrane surface of the base membrane.
2. The composite diaphragm according to claim 1, characterized in that: The base film of the composite diaphragm is a daramic film, the thickness of which is between 150 μm and 900 μm, the porosity of which is between 52% and 70%, and the pore size distribution range of which is between 0.001 nm and 600 nm.
3. The composite diaphragm according to claim 1, characterized in that: The inorganic particles are metal hydroxides; the particle size is 10nm to 50nm; Among them, the metal is one or more of magnesium, cobalt, nickel, and zinc combined with one or two of aluminum, iron, and chromium; the layered structure is a two-dimensional lamella structure, and the layer plate of a single lamella unit cell is 0.5nm×0.5nm~1.5nm×1.5nm; the thickness of a single lamella unit cell is 5~30nm, preferably 15~20nm.
4. A method for preparing the composite diaphragm according to any one of claims 1 to 3, characterized in that: The steps include: (1) dissolving an inorganic metal salt in water to obtain an inorganic metal salt solution; the inorganic metal salt in the inorganic metal salt solution is a combination of a divalent metal salt and a trivalent metal salt; the metal ion concentration ratio of the divalent metal salt to the trivalent metal salt in the inorganic metal salt solution is 2:1 to 4:1; the inorganic divalent metal salt is one or more of a magnesium salt, a cobalt salt, a nickel salt, and a zinc salt; the inorganic trivalent metal salt is one or more of an aluminum salt, an iron salt, and a chromium salt; (2) soaking the Daramic base film in the inorganic metal salt solution in step (1); (3) adding one or more of nitrogen-containing organic matter and / or ammonium salt to the solution in step (2), and then ultrasonicating or stirring for 0.5 to 2 hours to perform a solvothermal reaction; (4) Soaking the composite membrane obtained in step (3) in an alkaline solution of sodium hydroxide and / or potassium hydroxide having a pH value greater than or equal to 12 (preferably 12 to 14), then washing with a solvent and drying to obtain the alkali-resistant porous composite membrane.
5. The preparation method according to claim 4, characterized in that: The inorganic metal salt in the inorganic metal salt solution of step (1) is a combination of a divalent metal salt and a trivalent metal salt; the metal ion concentration ratio of the divalent metal salt and the trivalent metal salt in the inorganic metal salt solution is 2:1 to 4:1, preferably 3 to 4:1; the inorganic metal salt is one or more of metal nitrates, sulfates and chlorides; The soaking temperature in step (2) is 50-80° C., and the soaking time is 8-48 hours; the membrane area is 3 cm×3 cm to 6 cm×6 cm, and the molar concentration of the inorganic metal salt solution is 1 mol / L to 3 mol / L, preferably 1.5 to 1.8 mol / L; The nitrogen-containing organic matter in step (3) is one or more of urea, formamide, and ammonia water; the ammonium salt is one or more of ammonium sulfate and ammonium chloride; after addition, the molar concentration of the nitrogen-containing organic matter and / or ammonium salt in the solution is 6 mol / L to 9 mol / L, preferably 7 mol / L; The solvent thermal reaction temperature is 90° C. to 150° C., preferably 100° C., and the reaction time is 24 hours to 72 hours, preferably 72 hours.
6. The preparation method according to claim 4, characterized in that: Before soaking the Daramic base film in the inorganic metal salt solution in step (1) in step (2), the Daramic base film is cleaned. The cleaning method is as follows: 1) Soaking the Daramic base film in an organic solvent consisting of ethanol and methanol; wherein the mixed volume ratio of ethanol and methanol is 1:2 to 2:1; the soaking time is 3 to 6 hours, and the soaking temperature is 30 to 70° C.; 2) taking out the Daramic basement membrane from step 1) and soaking it in water; the soaking time is 3 to 6 hours, and the soaking temperature is 30 to 70° C.; 3) Repeat steps 1) to 2) 0-4 times, preferably 2-3 times; In the step (4), the composite membrane obtained by the solvothermal reaction in step (3) is immersed in sodium hydroxide and / or potassium hydroxide with a pH value greater than or equal to 12 (preferably 12 to 14), the immersion temperature is 30° C. to 50° C., preferably 40° C., and the immersion time is 48 hours to 96 hours, preferably 96 hours; In step (4), the composite membrane soaked in the alkaline solution is cleaned with a solvent, wherein the cleaning solvent is an ethanol aqueous solution with a volume concentration of 1:3 to 1:5; In step (4), the cleaned composite membrane is dried at a temperature of 30° C. to 60° C. for a drying time of 48 hours to 96 hours.
7. An application of the composite diaphragm according to any one of claims 1 to 3, characterized in that: The composite diaphragm is used in the process of electrolyzing alkaline water to produce hydrogen and electrolyzing alkaline water to produce oxygen.
8. A zero-gap alkaline water electrolysis device, characterized in that: The zero-gap alkaline water electrolysis device comprises a cathode end plate, a porous cathode gas diffusion electrode (GDE-cathode), an alkali-resistant composite diaphragm as described in any one of claims 1 to 3, a felt-like anode gas diffusion electrode (GDE-anode), and an anode end plate, which are arranged in sequence; wherein the porous cathode gas diffusion electrode and the felt-like anode gas diffusion electrode are hot-pressed on both sides of the alkali-resistant composite diaphragm as described in any one of claims 1 to 3.
9. The zero-gap alkaline water electrolysis device according to claim 8, characterized in that: The cathode end plate material is one of high-purity graphite plate, N4 high-purity nickel plate, TA2 titanium plate and 904L stainless steel plate; The anode terminal plate material is one of an N4 high-purity nickel plate with a 1-3 μm platinum layer plated on the surface near the felt-like anode gas diffusion electrode, a TA2 titanium plate with a 1-3 μm platinum layer plated on the surface near the felt-like anode gas diffusion electrode, a 904L stainless steel plate with a 1-3 μm platinum layer plated on the surface near the felt-like anode gas diffusion electrode, and a Hastelloy C276 with a 1-3 μm platinum layer plated on the surface near the felt-like anode gas diffusion electrode; The porous cathode gas diffusion electrode is sprayed with 1-3 mg / cm 2 The nickel-based catalyst is made of foamed nickel; the nickel-based catalyst is one or more of Raney nickel, nickel sulfide, NiMo alloy or NiAl; The porosity of nickel foam is 95% to 98% and the thickness is 0.32mm to 0.4mm; The felt-shaped anode gas diffusion electrode is a titanium felt with metal platinum plated on the surface; the thickness of the metal platinum plated layer is 50nm-2μm; the thickness of the titanium felt is 100μm-300μm; and the porosity of the titanium felt is 40%-80%.
10. The zero-gap alkaline water electrolysis device according to claim 8 or 9, characterized in that: The cathode gas diffusion electrode and the anode gas diffusion electrode are hot pressed on both sides of the alkali-resistant porous electrode diaphragm according to claim 1; the hot pressing temperature is 100° C. to 140° C., and the hot pressing time is 10 seconds to 1 minute; The alkaline water for electrolysis is a potassium hydroxide or sodium hydroxide aqueous solution with a concentration of 0.5 mol / L to 10 mol / L.
Citation Information
Patent Citations
Preparation method of inorganic nanoparticle composite membrane of polytetrafluoroethylene
CN112892246A
Preparation method and application of composite membrane for alkaline zinc-based flow battery
CN112928315A
Hydrotalcite in-situ growth composite membrane, and preparation method and application thereof
CN112928322A
Organic-inorganic composite membrane as well as preparation method and application thereof
CN114181426A
Composite membrane as well as preparation method and application thereof
CN114614039A